The use of digital technologies in social marketing: a systematic review. Issue 4 (9th June 2021) - Flaherty, Tina; Domegan, Christine; Anand, Mihir
Abstract : Purpose: With the explosion of digital technologies in contemporary daily life, fuelled by a pandemic and remote working, online learning and shopping and the proliferation of social platforms, much remains nebulous about the opportunities these technologies hold for social marketers beyond their previously documented use as communication and promotion tools. This paper aims to provide a rich examination of the variety of digital technologies used within social marketing and establish the scale of integration between digital technologies and social marketing. Design/methodology/approach: Following systematic literature review procedures, a systematic literature review through eight databases was conducted. The systematic review focussed on the assessment of social marketing studies that incorporated a wide range of mature and emerging digital technologies such as the internet, mobile platforms and social media channels. A total of 50 social marketing studies (2014–2020) were analysed. Findings: The review found that there have been major advancements in the technologies available to social marketers in recent years. Furthermore, the adoption of digital technologies by social marketers has evolved from a communication or promotion function where generic information is pushed to the citizen, towards the use of these technologies for a more personalised design, content and behaviour change intervention. In some studies, the digital technologies were the primary means for interactions and collaborations to take place. The review also found that digital technologies target more than the individual citizen. Digital technologies are used to target multi-level stakeholders, policy makers and partners as part of behavioural change interventions. Originality/value: Only two previous reviews have synthesised digital technologies and their use in social marketing. This review provides a recent depiction of the range and scale of integration within social marketing. Specifically, it demonstrates the expansion beyond a persuasive application to their use for research, segmentation and targeting, collaboration and co-creation, the product and facilitator of service delivery. Finally, this review provides a heat map to illustrate the integration between digital technologies and key concepts and criteria within social marketing.